Pulses Yield Gap Minimization: Consequences of CFLD-Pulses in India - S. K. Dubey; U. S. Gautam, Atar Singh (Indian Journal of Extension Education, 2022)
The present study is the analysis of large scale data (31949 ha area and 79873 farmers) generated through the CFLD on pulses across the major pulses growing states under the ICAR-ATARIs of Kanpur, Jodhpur, Pune, Jabalpur, Kolkata, Guwahati, Hyderabad, Bangalore and Patna. The present analysis represented the pulse crops of kharif (pigeon pea-5556 ha, black gram-6067 ha and green gram-2689 ha), rabi (chickpea-8376 ha, lentil- 3747 ha and field pea-1890 ha) and summer (green gram-3624 ha) seasons. The average performance data of CFLD were obtained for the above states during the cropping seasons of 2016-17 and 2017-18. Thus, CFLD data were analyzed from across minimum of 13 states (green gram) and maximum of 19 states (black gram). The major variables analyzed were average yield obtained from the check plots and demonstrations plots. These yields were computed for yield advantages and also compared with the reported district level, state level, National level yields and the potential yields of the respective crops in the given states (data procured from secondary sources for the year 2017-18). Accordingly the yield gaps and yield gap minimized at various levels were analyzed using appropriate methods and their degree of variation was also computed for the seasons and crops.